2016
DOI: 10.4028/www.scientific.net/msf.879.861
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameter Optimization of Fused Deposition Modeling for Helical Surfaces Using Grey Relational Analysis

Abstract: Fused Deposition Modeling (FDM), a fast growing rapid prototyping technology, is a process for developing physical objects by adding fused layers of materials according to a three dimensional CAD geometry. FDM can be used to produce parts with complex geometries. Hence it gains distinct advantages in industries. One of the major drawbacks of FDM is the reduced part quality measured in terms of dimensional accuracy, surface finish and mechanical characteristics. The major share of research literature related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Mohamed et al (2016b) proposed I-optimality criteria for the optimization of FDM process parameters. Anusree et al (2017) studied the effect of controlling factors on tensile strength, dimensional accuracy and surface roughness of helical surface of a FDM-fabricated part. Ideal parameter setting was obtained by grey relational analysis.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Mohamed et al (2016b) proposed I-optimality criteria for the optimization of FDM process parameters. Anusree et al (2017) studied the effect of controlling factors on tensile strength, dimensional accuracy and surface roughness of helical surface of a FDM-fabricated part. Ideal parameter setting was obtained by grey relational analysis.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…And the reason can be the difference in the desired responses and the difference in the selected material. Another reason could be other selected parameters because all parameters affect each other [23,25,27,28].…”
Section: Confirmation Testmentioning
confidence: 99%
“…The layer thickness of 0.2 mm, the Raster width of 0.55 mm, extrusion temperature 270°C, Bed temperature 100°C, and Printing speed 40 mm/s are optimal conditions. Anusree et al [28] analyzed the effects of four variables, including print speed, layer thickness, support material density, and raster width, on dimensional accuracy, tensile strength, and surface finish of FDM-processed helical surfaces using Taguchi and GRA methods. It was stated that the better dimensional accuracy, tensile strength, and surface finish were obtained by a minimum level of the layer thickness, in a print speed of 58 mm/s, and maximum level of raster width and rough support material.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was noted that the dimensions of the 3D printed parts were smaller than the CAD model because of the shrinkage during cooling of the material after the deposition of layer. Nidagundi et al [23], Anusree et al [24], and Wang et al [25] reported that the smallest layer height was determined as the optimal layer height level for the best dimensional accuracy levels of 3D printed ABS parts according to Taguchi's experimental designs. Unlike, the optimal level of layer thickness was decided to be medium level (0.178 mm) in other studies [19,26].…”
Section: Introductionmentioning
confidence: 99%